Requisitos exigidos nos processos de seleção de emprego no setor do comércio do município de Francisco Beltrão - PR - Antunes, Paula Regina (2014)
The process of selection and recruitment are intended to choose the professional that best meet the required profile for the vacancy to be filled at the company, using requirements and methods for evaluation of human behavior. However, the organizations, the desire to hire a candidate with higher qualification and best suited to the role profile, using aspects of research that does not aim to evaluate the fitness professional, violating the intimacy and privacy of the applicant. From this perspective, the overall goal of this research is to verify the requirements in the selection processes of candidates in the companies of the trade in the municipality of Francisco Beltran-PR industry. The study is qualitative and quantitative. The sample consisted of 139 companies identified from the Trade Union of the Municipality. Data collection took place from the 04th to 10th November 2014, by applying a questionnaire to the companies responsible for hiring the city trade sector. Data were analyzed using the statistical method of cluster, using the software SPSS 18. The results showed that the participants practice discriminatory conduct, requiring candidates personal and professional references (81%). The survey also revealed that 50% of companies require a good-looking candidates, as well as appropriate dress and behavior (74%) and 52% elect age as an important requirement for hiring, with 56% of participants perform in consultation bodies SPC and the credit bureau. With regard to the requirement of time in previous employment, 74% of participating companies consider as an important requirement in hiring. Furthermore, 65% would not hire pregnant women candidates and 84% consider the use of chemicals. We conclude that, despite the constitutional protection and all existing legal apparatus, the companies of the trade of Francisco Beltran sector during the pre-contractual stage practice discriminatory acts.